Análise tridimensional pelo método dos elementos finitos dos esforços nos elementos estruturais de um edifício alto com estrutura de aço sujeito à ação de forças laterais e com transição no sistema de estabilização lateral - Ana Maria Drummond Stehling (2005)
In practice, in high-rise buildings with steel structures, functional and architectural reasons sometimes cause the occurrence of abrupt transitions in the lateral bracing system, characterized by the suppression of bracing panels in the lower stories of thebuilding. As a consequence, the reinforced concrete floor slabs become responsible for the transmission of the wind loads from the regions of the suppressed panels to the remainder, and present high localized stresses, which can cause problems related to the serviceability limit states. This work studies the stresses in the floor slabs of a twentystory building, caused by the transition in the lateral bracing system. The building has dimensions in plant of 30 m by 9 m, full reinforced concrete slabs with 8 cm of thickness and beams, column and diagonals made of steel. The transversal lateral bracing system is composed of three equal braced frames, symmetrically positioned, two in each extremity and the third in the center of the building. The longitudinal lateral bracing system is composed by rigid frames. The building is analyzed with the consideration of three distinct situations. In the first one, no transition is done in the lateral bracing system. In the second one, the diagonals of the central braced frame are suppressed in the first story. In the third situation, the diagonals of the central braced frame are suppressed in the first and second stories. The structures are threedimensionally modeled, using the Finite Element Method, and are analyzed by the software SAP2000. A second-order analysis is done considering the P- effect. The outputs of the analyses of the three structures are compared to evaluate the impacts of the transitions on the slabs and on the other elements constituting the structure of the building. Two other models are used to analyze the structure when the transition occurs in the first story, a simplified model which presents very conservative results, and a three-dimensional model, in which case the slabs are modeled as rigid diaphragms. The objective of the work is to show the impacts that transitions in the lateral bracing systems cause on slabs, beams, columns and diagonals that constitute the structure of the building